PENERAPAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN LITERASI SAINS DAN KUALITAS ARGUMENTASI SISWA PONDOK PESANTREN DAARUL ULUUM PUI MAJALENGKA PADA DISKUSI SOSIOSAINTIFIK IPA - Djohar Maknun (UIN Sumatera Utara Medan, 2014)
This study was conducted to apply science learning with contextual approach to improving scientific literacy and the quality of students' arguments in a discussion of issues socio scientific. The study was conducted in MTs Daarul Uluum Majalengka PUI, involving 33 students of Boarding Schools Daarul Uluum Majalengka PUI. The findings of this initial study showed no learning materials linked to real-life situations of students, according to the context of people's lives around. Efforts to improve scientific literacy and the quality of the students argument has never been done in learning science. Implementation developed contextual learning done in class and in the field. Data were collected through a needs analysis, documentation, observation, interviews, tests, and questionnaires. Qualitative data analysis is described in accordance with a research focus. Quantitative data were processed using N-gain, differential test and correlation test. The results showed that the application of contextual learning can be implemented with various methods and evaluation. It was also found that contextual learning through discussion of issues socio scientific can improve scientific literacy and the quality of students' arguments. Correlation coefficient of 0.850 means there is a strong relationship between the quality of argumentation in the discussions pre discussion with post discussion socio scientific issue. Contextual learning is linked to the issue of sosio scientific IPA is a new and exciting enough student interest. Keywords: contextual learning, scientific literacy, the quality of the arguments, issues and IPA socio scientific